Exercise oncology clinical trials during treatments: a commentary to address the safety concerns of human subjects regulatory reviewers and committees - Caru, Maxime; Zaorsky, Nicholas G.; Sturgeon, Kathleen M.; Potiaumpai, Melanie; Gordon, Brett; Doerksen, Shawna; Schmitz, Kathryn H. (Supportive care in cancer, 2024)
Exercise oncology clinical trials contribute to the advancement of our scientific knowledge and to the safety and care of patients diagnosed with cancer. Nevertheless, regulatory reviewers and committees may not be familiar with the well-documented long-term health benefits and safety of the regular practice of physical activity. Moreover, they may not see how the benefits outweigh the risks in the context where patients diagnosed with cancer are typically seen as vulnerable. Therefore, we would like to provide a purpose-built overview of exercise oncology clinical trials for members involved in institutional review committees, including the Scientific Review Committee (SRC), the Institutional Review Board (IRB), and the Data Safety Monitoring Committee (DSMC) to facilitate a greater understanding of the safety and benefits of physical activity during cancer treatments. Communication is key to improve the success of exercise oncology clinical trials, which are vital for patients diagnosed with cancer.